Pemanfaatan Website dan Media Sosial Perpustakaan dalam Layanan Referensi Perpustakaan Perguruan Tinggi - Meilita, Weni (UI Scholars Hub, 2020)
The reference service in the college library is an important service for users. The existence of a reference service makes it easier for the community to conduct research and learning. Current technological developments affect various elements including services in the Library. Website and social media as one of the technological development products used by libraries to support reference services. In this study, researchers conducted research on websites and social media in one library in Indonesia and three libraries abroad. This research uses descriptive research method with a qualitative approach with the object of research is the website and social media in four Higher Education Libraries. The findings from the study provide an overview of websites at overseas tertiary libraries that are already very good at providing reference services via websites and social media to their users.